Does auditor choice matter to foreign investors? Evidence from foreign mutual funds worldwide - Chou, Julia; Zaiats, Nataliya; Zhang, Bohui (Journal of Banking & Finance, 2014)
This study explores whether a firm’s auditor choice affects its ability to access foreign equity capital. Using the equity holdings of 35,665 foreign mutual funds from 30 countries for the period 1998–2009, we find evidence that appointing a Big 4 auditor is associated with the increased level of foreign mutual fund ownership in firms. Our results are robust when conditioned on firm-level information asymmetries, country-level information disclosure quality, and when employing the Enron–Andersen fiasco as the natural experiment. Furthermore, appointing Big 4 auditors is particularly important for firms to attract foreign capital during the 2008 global financial crisis.